PERLINDUNGAN HUKUM TERHADAP SERIKAT PEKERJA BERDASARKAN UNDANG UNDANG NO 21 TAHUN 2000 DAN UNDANG UNDANG KETENAGAKERJAAN - Yanu Ferry Mulyono; Sugeng Hadi Purnomo (Gapenas Publisher, 2022)
In carrying out and carrying out the development of a company there must be several factors such as capital, nature, and labor factors. In the course of history, it has been proven that the role of trade unions/labor unions in fighting for the rights of their members is very large, so that workers/labourers have felt the benefits of an independent and consistent trade union/labor union organization in fighting for workers' rights. In this paper, the author uses a normative research method that examines law from an internal perspective with the object of research being legal norms. One form of protection for workers is a trade union or labor union. Another function of the trade/labor union is as a party to the settlement of industrial disputes, namely differences of opinion which result in a conflict between the entrepreneur or a combination of employers and workers/labor or a trade/labor union due to disputes over rights, disputes over interests, and disputes over termination of employment. and disputes between trade unions/labor unions in only one company. Here the existence of law is only as a tool to secure the power of the owners of capital under the guise of moralists. It is not only the law that is used as a mere tool, but the role of the government, which should carry out the functions of supervision, prosecution, and the function of setting policies, cannot act as it should. It seems that the law which was originally used as a means of control cannot be used optimally in serving the interests of the community, and especially for workers who want to uphold the law (the rule of law). Here the effectiveness (enforcement) of the law begins to be questioned, and in particular the level of success in providing services to the industrial community